Graphene Materials for Miniaturized Energy Harvest and Storage Devices. Issue 1 (5th November 2021) - Li, Xiangyang; Wang, Ying; Zhao, Yang; Zhang, Jing; Qu, Liangti
Abstract : The development of miniature energy harvesting and storage devices with considerable performance is urgently needed for the increasing demand of diverse electronics that require portable and wearable functions. With a unique 2D structure, graphene material possesses numerous fascinating physical and chemical properties which endow it as promising candidate component or building block to boost such miniature devices system with superior performance and multifunctionality, including but not limited to active material, flexible substrate, and electrically conductive additive. In this review, the recent advances of graphene‐based materials for miniature energy harvesting and storage devices are summarized, including solar cells, mechanical energy harvesters, moisture and liquid flow generators, batteries and electrochemical capacitors, and their integrated devices. The design strategies of active electrodes and devices in performance improvement and functions are specially emphasized. Finally, the challenges and future directions of graphene materials in microdevices are also provided. Abstract : This review summarizes the progress of graphene materials for miniaturized energy harvest and storage devices, including solar cell, mechanical energy harvesters, moisture and liquid flow generators, batteries and electrochemical capacitors, and their integrated devices. The challenge and prospective of graphene‐based electrode materials and microdevices in performance improvement, microfabrication, and integration technology are also provided.